África na Senzala Latino-Americana Utopias de escravos rebeldes: Brasil e Cuba, década de 1830 - Lienhard, Martin (Africana Studia, 2020)
Based on the close-reading of trial documenlation, this arlicle about two slave uprisings in a Brazilian and in a Cuban plantation, which took place in lhe thirlies of lhe nineteenth century, intends to reveal the cultural and ideological universe - specially the recreation of originally African practices and altitudes - of the rebel communities.